MENGGALI MAKNA ASAS LEGALITAS DAN PERKEMBANGANNYA DI INDONESIA - Tahir, ach, (Al-Mazaahib: Jurnal Perbandingan Hukum, 2018)
The principle of legality is a very fundamental principle in Positive Criminal Law and Islamic Criminal Law. The Indonesian Criminal Code Bill recognizes the principle of material legality (not absolute), so the consequence, even though it is not regulated in the legislation, is that someone's actions deserve to be punished. A person can be punished by referring to the law that lives in society. The principle of legality in positive law can actually be deviated, provided that the criminal act threatens order and security. In Islamic Criminal Law, the principle of legality can also be deviated with a note that it threatens public order and security